Semantic Richness Effects in Spoken Word Recognition: A Lexical Decision and Semantic Categorization Megastudy - Goh, Winston D.; Yap, Melvin J.; Lau, Mabel C.; Ng, Melvin M. R.; Tan, Luuan-Chin (Frontiers in Psychology, 2016)
A large number of studies have demonstrated that semantic richness dimensions (e.g., number of features, semantic neighbourhood density, semantic diversity, concreteness, emotional valence) influence word recognition processes. Some of these richness effects appear to be task-general, while others have been found to vary across tasks. Importantly, almost all of these findings have been found in the visual word recognition literature. To address this gap, we examined the extent to which these semantic richness effects are also found in spoken word recognition, using a megastudy approach that allows for an examination of the relative contribution of the various semantic properties to performance in two tasks: lexical decision and semantic categorisation. The results show that concreteness, valence, and number of features accounted for unique variance in latencies across both tasks in a similar direction – faster responses for spoken words that were concrete, emotionally valenced, and with a high number of features – while arousal, semantic neighbourhood density, and semantic diversity did not influence latencies. Implications for spoken word recognition processes are discussed.